ORTAOKUL ÖĞRETMENLERİNİN ÖZERKLİK (OTONOMİ) DÜZEYLERİ, MESLEKİ STATÜ ALGILARI VE İŞ DOYUMLARI ARASINDAKİ İLİŞKİ - POLAT, ESRA (Fırat Üniveristesi, 2024)
Bu çalışmanın genel amacı; ortaokul öğretmenlerinin özerklik düzeyleri, mesleki statü algıları ve iş doyumları arasındaki ilişkiyi belirlemektir. Araştırmada OECD tarafından uygulanan TALIS 2018 araştırmasında, Türkiye'den toplanan 3952 ortaokul öğretmenine ait veriler kullanılmıştır. Ortaokul öğretmenlerinin özerklik düzeyleri ve mesleki statü algıları ile iş doyumları arasındaki ilişkiyi inceleyen bu araştırmada, ilişkisel tarama modeli benimsenmiştir. Verilerin analizinde betimsel analizler yapılmış, ayrıca t testi, Pearson Korelasyon Analizi ve Çoklu Regresyon Analizi teknikleri kullanılmıştır. Yapılan analizler sonucunda; ortaokul öğretmenlerin özerklik algılarının genel olarak yüksek düzeyde, iş doyumu algılarının orta düzeyde, mesleki statü algılarının ise düşük düzeyde olduğu sonucuna ulaşılmıştır. Ortaokul öğretmenlerinin özerklik düzeyleri, öğretmenlik mesleğinin statüsüne ilişkin algıları ve iş doyumlarının cinsiyet değişkenine göre anlamlı farklılık gösterdiği tespit edilmiştir. Özerklik ve iş doyumu değişkenlerindeki fark kadın öğretmenler lehine iken; mesleki statü algısındaki farkın erkek öğretmenler lehine olduğu görülmüştür. Öğretmenlerin iş doyumlarında eğitim düzeylerine göre lisans mezunlarının lehine anlamlı bir farklılık görülürken; özerklik ve mesleki statü algısında anlamlı bir farklılık bulunmamaktadır. Korelasyon analizi sonuçlarına göre, özerlik ve iş doyumu arasında pozitif düşük; mesleki statü algısı ve özerklik arasında pozitif düşük, mesleki statü algısı ve iş doyumu arasında ise pozitif orta düzeyde anlamlı ilişki olduğu görülmüştür. Regresyon analizi sonucuna göre öğretmenlerin özerklik düzeyleri ve mesleki statü algıları birlikte, iş doyumlarındaki ortaya çıkan varyansın yaklaşık %20,4'ünü açıklamaktadır. Başka bir ifadeyle; öğretmenlerin özerklik düzeyleri ve mesleki statü algıları iş doyumlarının anlamlı yordayıcılarıdır. Sonuç olarak özerlik, mesleki statü algısı ve iş doyumu birbirleriyle ilgili değişkenlerdir. Eğitimde başarının, kalitenin ve öğretmenlerin iş doyumunun artması isteniliyorsa; öğretmene özerklik imkânı sunulmalı, yüksek mesleki statü verilmelidir.

The general aim of this study is to determine the relationship between middle school teachers' autonomy levels, perceptions of professional status, and job satisfaction. The study used data from 3,952 middle school teachers collected from Turkey as part of the OECD's TALIS 2018 survey. This research, which examines the relationship between middle school teachers' autonomy levels, perceptions of professional status, and job satisfaction, adopted a relational survey model. Descriptive analyses were conducted in the analysis of the data, and t-tests, Pearson Correlation Analysis, and Multiple Regression Analysis techniques were also used As a result of the analyses, it was concluded that middle school teachers' perceptions of autonomy are generally high, their job satisfaction perceptions are moderate, and their perceptions of professional status are low. It was found that middle school teachers' levels of autonomy, perceptions of the status of the teaching profession, and job satisfaction showed significant differences according to the gender variable. The differences in autonomy and job satisfaction variables were in favor of female teachers, while the difference in perceptions of professional status was in favor of male teachers. A significant difference in teachers' job satisfaction was found in favor of bachelor's degree graduates according to their education levels, while there was no significant difference in perceptions of autonomy and professional status. According to the results of the correlation analysis, there was a low positive relationship between autonomy and job satisfaction; a low positive relationship between perceptions of professional status and autonomy; and a moderate positive relationship between perceptions of professional status and job satisfaction. According to the results of the regression analysis, teachers' autonomy levels and perceptions of professional status together explained approximately 20.4% of the variance in job satisfaction. In other words, teachers' levels of autonomy and perceptions of professional status are significant predictors of job satisfaction. In conclusion, autonomy, perceptions of professional status, and job satisfaction are interrelated variables. If success, quality, and teachers' job satisfaction in education are to be increased, teachers should be provided with opportunities for autonomy and given high professional status.
The relationship between middle school teacher's autonomy levels, perceptions of professional status and job satisfaction
Keywords: Eğitim ve Öğretim